Efeitos da Reeducação Postural Global na Hipercifose e nas Variáveis Respiratórias de Idosos Relato de Dois Casos - Itokazu, Caroline Ataíde [UNESP]; Sotolani, Fabiana Sabino [UNESP]; Ambrozin, Alexandre Ricardo Pepe [UNESP]; Navega, Marcelo Tavella [UNESP] (My University, 2011)
Examine the effects Global Postural Reeducation, (GPR) in hyperkyphosis and respiratory variables in the elderly was the objective in the research. For this, two elderly participated, one is 62 years old (voluntary 1) and another is 66 years old (voluntary 2), without lung, heart, kidney and/or skeletal-muscle diseases diagnosed. The volunteer have been assessed for Quality of Life (QOL) through the questionnaire SF-36, the degree of toracic kyphosis, the muscular respiratory strength and the thoracic-abdominal mobility. The GRP treatment consisted in eight sessions applied, once one hour each session. After the eight sessions the volunteer were reevaluated. The data concerning assessments before and after treatment were analysed describly. According to the results there was an improvement in the degree of kyphosis in both volunteers, highlighting voluntary 2. Respiratory variables also improvements after treatment. In relation to the Quality of life in most areas there has been an increase in scores indicating improved QOL. These data showed that the GPR has been effective to decrease the level of kyphosis, improves respiratory variables and the quality of life in the elderly treated. However, further work with a greater number of subjects must be carried out to analyze the effectiveness of therapy in the elderly.

Analisar os efeitos da Reeducação Postural Global (RPG) no grau de hipercifose e variáveis respiratórias em idosos foi objetivo deste estudo de casos. Para tanto, participaram desta pesquisa duas idosas, uma de 62 anos (voluntária 1) e outra de 66 anos (voluntária 2), não portadoras de doenças pulmonares, cardíacas, renais e/ou músculo-esqueléticas. As voluntárias foram avaliadas em relação a qualidade de vida (QV) por meio do questionário SF-36, o grau de cifose torácica, a força muscular respiratória e a mobilidade tóraco-abdominal. O tratamento de RPG foi aplicado em oito sessões com duração de uma hora cada sessão. Após as oito sessões foram reavaliadas. Os dados referentes as avaliações antes e após tratamento foram analisados descritivamente. De acordo com os resultados houve melhora no grau de cifose de ambas as voluntárias destacando-se a voluntária 2 que apresentou redução de 16o. As variáveis respiratórias também apresentaram melhoras após o tratamento. Em relação à qualidade de vida, na maioria dos domínios houve aumento nas pontuações, o que indica melhora da QV. Estes dados permitem concluir que a RPG foi eficaz para diminuição do grau de cifose, melhora das variáveis respiratórias e da qualidade de vida das idosas tratadas. Entretanto, novos trabalhos com um maior número de sujeitos devem ser realizados para analisar a eficácia da terapia em idosos.
Effects of Global Postural Reeducation in the Hyperkyphosis and in the Respiratory Variables of Elderly Woman – Report of Two Cases
Keywords: RPG; Respiratória; hipercifose torácica